The visual politics of corruption. Issue 12 (2nd December 2019) - Hellmann, Olli
Abstract: Despite the fact that corruption is essentially invisible, communication campaigns by the global anti-corruption industry regularly feature photographic images. So far, however, we do not know much about the narratives that are encoded in these images. Through the theoretical lens of postcolonialism, this paper takes a first step towards developing an understanding of the visual representation of corruption. Specifically, the paper applies semiotic and iconographic methods to two photography competitions run by Transparency International – the major non-governmental player in the anti-corruption industry. The analysis shows, first, that the anti-corruption industry reinforces colonial stereotypes, suggesting that the 'sinful' and 'irrational' Global South is waiting to be civilised by the North. Second, through its visual imagery, the anti-corruption industry also emphasises ideas of a 'humanitarian family', which serves to cover up the North's role in transnational webs of corruption. These findings are triangulated with semiotic/iconographic analyses of the Transparency International logo and the Corruption Perceptions Index map.